Implementation status and challenges of telemedicine service (specialists’ consultation) for correctional homes in Kolkata: A mixed method study - Subhosri Saha; Soma Chakrabarti; Sreetama Chakrabarti; Somnath Naskar; Mausumi Basu (Asian Journal of Medical Sciences, 2025)
Background: The State Administration of West Bengal, India has recently operationalized telemedicine (TM) services for specialist consultation at eight central correctional homes (CHs) with the aim of improving overall well-being and medical care of the inmates.